(untitled) (Филолошке студије, 2019)
In the paper an attempt is made to analyze, on the material of literature and the history of everyday life, the mechanism of identification in the Slovenian culture. On the base of their native language the Slovenians have been carrying on their own identification by means of contrasting and at the same time uniting the general Slav and the unique Slovenian selfconsciousness. Through the category of space in the Slovenian consciousness the connection and unity of the whole Slovenian people were realized, especially of the parts that at different periods of time turned to be beyond their native ethnographic territory. The ceremony, including the transitional one, in the XIX – XX centuries helped to identify the cultural and artistic achievements of the Slovenian people that had comprehended the value of the unity if its culture. In connection with that the motive of the cultural memory arises in the paper – the ceremony of enthroning that has been known since the VII century and has acquired its importance in modern literature.